Social Media and Library Marketing: Experiences of KN Raj Library - Sriram, V. (DESIDOC Journal of Library & Information Technology, 2016)
Marketing is essential for attracting potential customers and retaining existing customers. Libraries and information centres are also increasingly entering into the foray of library marketing and public relations using all available means. The various Web 2.0 and social media tools are very convenient for the libraries to market their resources and services. The paper explains various popular social media tools and argues for their extensive use in libraries for marketing and publicity. How these social media tools can be effectively put to use in libraries for marketing its resources and services are explained by illustrating services in the KN Raj Library of Centre for Development Studies, Thiruvananthapuram. DOI: 10.14429/djlit.36.3.9810